«
  
»

Sendo f(x+3)=2x+3, determine f(2x+3).



RESOLVENDO

Vestibulanda,

Como apresentada, verifica-se que a função é do 1º grau!

Com isso, \( f(x) = ax + b \),

\( \\ f(x) = ax + b \\ f(x + 3) = a(x + 3) + b \\ 2x + 3 = ax + (3a + b) \\ \begin{cases} \boxed{a = 2} \\ 3a + b = 3 \Rightarrow 6 + b = 3 \Rightarrow \boxed{b = - 3}\end{cases} \)

Isto é, \( f(x) = 2x - 3 \)

\( \\ f(x) = 2x - 3 \\ f(2x + 3) = 2(2x + 3) - 3 \\ f(2x + 3) =4x + 6 - 3 \\ \boxed{\boxed{f(2x + 3) = 4x + 3}} \)



O que achou desse conteúdo? Deixe seu comentário
TAREFAS SIMILARES: